Influence brand trust, brand equity, and brand image toward Sharia bank customer loyalty - Kusnandar, Acu (Edelweiss Applied Science and Technology, 2025)
Customer loyalty to a brand is a concept considered important, especially in conditions where competition is fierce and growth is low. This research aims to determine whether brand trust, brand equity, and brand image influence the loyalty of customers in Islamic banks. The research method used is descriptive and verificative, with data collection through questionnaires processed with the help of SPSS. The results of the study indicate a positive influence of brand trust on customer loyalty. This means that the better the brand trust, the higher the customer loyalty. There is also a positive influence of brand equity on customer loyalty. This means that the more effective the brand equity, the higher the customer loyalty. Additionally, there is a positive influence of brand image on customer loyalty. This means that the more positive the consumer's brand image, the higher the customer loyalty. The influences of brand trust, brand equity, and brand image on customer loyalty are evident. This means that the better the brand trust, brand equity, and brand image, the better the customer loyalty. Customer loyalty can be explained through the variables of brand trust, brand equity, and brand image.